Russian Presence in Georgian Film Dubbing: Scales of Inferiority. (August 2015) - Sherouse, Perry
<x xml:space="preserve">Abstract</x> In Georgia, a law enacted on January 1, 2011 mandated that all foreign language films possess either Georgian dubbing or subtitling for public film showings. This legal measure was targeted at removing Russian presence in film language, as part of then‐President Saakashvili's shift away from alignments with Russia and Russianness in Georgian public cultural life. This article investigates the ideological and institutional dimensions of the creation of a new film dubbing industry in Tbilisi for an audience that was critical of it. Russian technical and artistic expression remained the rubric against which Georgian dubbing was compared. Soviet and Russian forms, which continue to permeate the Georgian social world, have structured expectations about "quality" or "art" in dubbing. Additionally, evaluations of dubbing as a form of linguistic mediation described Georgian language as in a relationship of inferiority with respect to Russian, which has long been linked to high‐culture forms of sociotechnical mediation. The emergence of a new film dubbing industry in Georgia draws out a number of contradictions in the ways that the institutional calibration of foreignness inheres in labor, aesthetics, and technical forms.